Abusive supervision in government - Caillier, James Gerard 1969- (Lanham, Maryland Lexington Books, 2021)
"The author uses a mixed-method approach to contend that organizational and subordinate factors either increase or decrease the presence of abusive supervision and that abusive supervision adversely affects government employees. A mixed-method approach is also used to argue that problems concerning the abusive supervision reporting process exists"--Provided by publisher.
Abusive Supervision Defined -- Antecedents of Abusive Supervision -- The Impact of Abusive Supervision on the Target -- Reporting Abuse Supervision -- Retaliation Against Reporters of Abusive Supervision -- Issuance of Corrective Actions After Reporting Abusive Supervision -- Workplace Aggression Policies -- Future Research Avenues Regarding Abusive Supervision.
Includes bibliographical references and index.
Keywords: Abuse of administrative power; Supervisors; Civil service -- United States -- Personnel management